Transforming Education for Sustainable Futures: Intersecting dynamics of food, water, livelihoods and education in the COVID-19 pandemic - Kgosietsile Velempini; Heila Lotz-Sisitka; Injairu Kulundu; Lwanda Maqwelane; Anna James; Gibson Mphepo; Phila Dyantyi; Esthery Kunkwenzu (Environmental Association of Southern Africa, 2022)
Since 2019, the COVID-19 pandemic has posed challenges to but also highlighted the urgent need for transforming education for sustainable futures. The purpose of this article is to share insights gained from a southern African study on intersecting influences of water, food, livelihoods and education, and what they mean for Education for Sustainable Development going forward. The interest is to learn from this study in ways that can inform transformation of education for sustainable futures in southern Africa going forward. The study involved a number of early career researchers in SADC countries, and was conducted via an online approach during the early days of the pandemic. It followed a qualitative research design, employed document analysis, interviews and questionnaires, and drew on a systems perspective to inform analysis. The findings are as relevant today as they were in the pandemic, and point to the importance of giving attention to intersecting issues that affect education. The study highlights six transformative praxis pathways for transforming education for sustainable futures.